PENERAPAN PRAKTIK IBADAH DAN PEMBENTUKAN KARAKTER SISWA SDN 054883 NAMO MBELIN - Tri Liana Wati (CV. Arsy Persada Quality, 2025)
This research aims to describe the implementation of character education, religious values, aspects of worship in lower class students at SDN 054883 Namo Mbelin. The research subjects were lower class students, lower class teachers, and school principals. Data collection uses observation, interviews, documentation, and self-assessment questionnaires. Data analysis uses quantitative and qualitative descriptive analysis techniques. Testing the validity of the data uses triangulation of sources and techniques. The research results show that the internalization of religious values ​​in aspects of worship is done through strategies: 1) getting used to regular worship at school. 2) exemplary practice of worship by the teacher. 3) providing advice on exemplary stories. 4) attention and supervision, with praise, appreciation, and assistance in worship activities by the teacher. 5) conditioning of the physical environment and religious atmosphere. The inhibiting factors are teacher discipline and lack of parental supervision at home. The assessment results show that 53.08% of lower class students at SDIT Salsabila 5 are accustomed to washing before worship and praying during ablution; 44.62% are accustomed to praying five times a day; and 44.61% are used to dhikr and praying after prayer.